2017
DOI: 10.1590/1678-4324-2017160157
|View full text |Cite
|
Sign up to set email alerts
|

Gonadosomatic index and some hematological parameters in African catfish Clarias gariepinus (Burchell, 1822) as affected by feed type and temperature level

Abstract: The purpose of the current study was to examine the effects of different feeds/nutrients and temperature on the gonadal development of Clarias gariepinus. The gonadosomatic index (GSI) HCT (29.06 ± 3.54%), PLT (90.75 ± 9.18/mm3), and MCV (118.08 ± 10.3 g/l). Fish meal diet revealed the most significant (p<0.05) increase in weight gain, female GSI, and also exerted significant increases on most of the blood parameters. This study revealed that animal-based protein diet and temperature around 28℃ were the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In this work, GSI was highest significantly in fish receiving the control feed which was similar to fish receiving other turmeric-supplemented feeds except for F, B, E and C. The result indicated that the inclusion of turmeric did not impose any reproductive advantage over fish on the control diet. This is evident in the lack of significant difference in the fecundity of all categories of fish across the experiment and also, in the presence of completely immature gonads even among fish on some turmeric-supplemented diets (B, F, G and H) 37,39 stated that fecundity could vary within the same species and even size depending on the feed intake among members. Thus, restricted consumption of the experimental diet might have limited turmeric intake below what could sufficiently cause significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, GSI was highest significantly in fish receiving the control feed which was similar to fish receiving other turmeric-supplemented feeds except for F, B, E and C. The result indicated that the inclusion of turmeric did not impose any reproductive advantage over fish on the control diet. This is evident in the lack of significant difference in the fecundity of all categories of fish across the experiment and also, in the presence of completely immature gonads even among fish on some turmeric-supplemented diets (B, F, G and H) 37,39 stated that fecundity could vary within the same species and even size depending on the feed intake among members. Thus, restricted consumption of the experimental diet might have limited turmeric intake below what could sufficiently cause significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…The GSI and fecundity are believed to be very important measures that define the reproductive capacity of fish 36,37 . GSI could reflect the changes in the nutritional and energy status of fish while variations in the GSI and fecundity are pointers to the reproductive season of the fish and the incidence of spawning 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Determination of size structure and gonadosomatic index: The gravid females were dissected and the ovaries were detached and weighed to the nearest 0.0l g for gonadosomatic index (GSI) study. The data on the body and gonad weights were used to compute the gonadosomatic index according to Al-Deghayem et al 16 :…”
Section: Number Of Females Sex Ratio = Number Of Malesmentioning
confidence: 99%
“…The demand for fish protein, essential amino acid, and fatty acid grows along with the population throughout the world as well as its preference for fish and the health advantages associated with its consumption (Desai et al, 2018;Kobayashi & Park, 2018). In this group is the tilapia, a common designation of cichlids fish species, found in America, Asia and Africa, where it can be considered the most important freshwater fish (Al-Deghayem et al, 2017). Although 22 species are commercially grown, Nile tilapia (Oreochromis niloticus), NT, represents 90% of the commercial production (Miranda et al, 2010) .…”
Section: Introductionmentioning
confidence: 99%